Investigating the effect of customers' education level on loyalty and trust (Case study: Alborz Province Export Bank) - Sohrabi, Shahla (2021)
The purpose of this study is to determine the effect of customer participation on customer loyalty with the mediating role of trust by considering the effect of literacy level. This research is descriptive-survey in terms of data collection method and applied in terms of purpose. The statistical population of the present study included all customers with different levels of literacy in Bank Saderat. Using Cochran's formula, the sample size required for the study was 196 people. The collection tool in this study was a questionnaire of Chen et al. The reliability of these questionnaires was confirmed using Cronbach's alpha coefficient. Amos23 software was used to analyze the collected data. The results showed that customer participation has a significant impact on customer loyalty. In addition, as the level of literacy of customers increases, their level of cooperation and trust increases or decreases. Trust also plays a mediating role in customer engagement, which affects customer loyalty